BIBLIOMETRIC ANALYSIS OF ENTREPRENEURSHIP EDUCATION IN SCOPUS-INDEXED JOURNALS - Sultono, Sultono; Barliana, M Syaom; Aryanti, Tutin; Suryadi, Dedy (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2025)
The aim of this study is to understand the roles, trends, and development of research in entrepreneurship education.  The method used is bibliometric analysis with the help of tools such as OpenRefine, VOSViewer, MS Excel, and Bibliometrix. These tools were used to analyze document distribution per year across different countries, institutions, journals, authors, topic trends, and keyword co-occurrences. The search was conducted on August 10, 2024, the literature search was conducted by entering words based on the title, abstract and keywords "education" AND "entrepreneurship", with restrictions in the data search, namely for the type of document in the form of research journal articles from 2016 to 2024 with limited criteria, data was obtained as much as 2,592 documents.The results of this study show a growth in the publication of articles on entrepreneurship education over the past nine years, with an average annual increase of more than fifteen percent. However, a decline was observed in 2019-2020. China is the most productive country in publishing articles related to entrepreneurship education, while the most productive institution is Universitas Negeri Jakarta from Indonesia. The top journal in this field is Education and Training Journal. Author co-occurrence analysis reveals two major networks of authors, led by Wibowo A and Wang J, respectively. Based on the data collected, the most frequently appearing keywords are "entrepreneurship" and "entrepreneurship education."  The latest topic trends related to entrepreneurship education include terms such as "innovation and entrepreneurship education,” "innovation and entrepreneurship," and "evaluation models.” Innovation and evaluation models become the current trend in this research area. This study can be useful for identifying research gaps regarding the development and implementation of entrepreneurship education, with the latest trends focusing on innovation and evaluation models.  Based on the data search, further comprehensive studies on the integration of entrepreneurship education, vocational education, and digital technology are needed.  According to the analyzed Scopus metadata, research on the integration of these fields is still very limited.